Utilization of Cockle Shell (Anadara granosa) Powder as Partial Replacement of Fine Aggregates in Cement Brick - Sainudin, Muhammad Shabery; Othman, Nor Hazurina; Ismail, Nurul Nabilah; Wan Ibrahim, Mohd. Haziman; A. Rahim, Masazurah (International Journal of Integrated Engineering, 2020)
Waste from fishery sector such as seashells are widely used in construction and building materials in order to reduce waste quantity. This study investigates the utilization of cockle shell powder (CSP) as partial replacement for fine aggregates in producing cement brick (CB). Bricks specimen are designed with three different percentages of 5% (CSP5CB), 10% (CSP10CB) and 15% (CSP15CB) replacements including control cement brick (CCB). An analysis conduct in this study are included sieve and specific gravity for materials testing while compressive strength, density and water absorption are for harden specimens. A rectangular brick shape specimen with 200mm Ã— 100mm Ã— 100mm in volume were used then cured using tap water for 7 and 28 days. The result revealed that compressive strength for specimens containing CSP are higher compared to CCB specimens. Besides that, CSP brick given a higher density with 2381.25 kg/m3 and lower water absorption 0.31% contrast from control specimens. According to overall data collected, the optimum composition for CSP in cement brick was 5% which indicated higher compressive and lower water absorption. Thus, the incorporation of CSP as sand replacement in bricks could improve and enhance physical and mechanical developments of bricks with the increment of curing time.